Aflasafe BF01 product for Burkina Faso and potentially 10 other countires in the Sahel - CGIAR Research Program on Agriculture for Nutrition and Health (2017)
Aflasafe BF01 a biocontrol product developed for use in maize and groundnut in Burkina Faso, was approved by the regulatory authority CSP-CILSS. Now the product is available for commercial use. The product is commercialized by the company Elephant Vert